ER stress sensors at the ER-mitochondrial interface, controlling mitochondrial health in neurodegenerative diseases - Kunja, Chaitanya; Kumar, Vaishali; Kodam, Pradeep; Gopu, Chamundeshwari Devi; Maity, Shuvadeep (Frontiers in Neuroscience, 2025)
The endoplasmic reticulum (ER) and mitochondria are essential organelles that interact closely at specialized sites known as ER-mitochondria-associated membranes (MAMs). MAM is enriched with proteins from both the ER and mitochondria. ER stress sensors—inositol-requiring enzyme 1 (IRE1) and protein kinase RNA-like ER kinase (PERK) — are traditionally recognized for their roles in the unfolded protein response (UPR), which mitigates proteotoxic stress. However, recent studies reveal their non-canonical functions at MAMs, where they regulate calcium signaling, mitochondrial dynamics, and apoptosis through interactions with MAM-resident proteins. Disruption of these pathways is implicated in various diseases, particularly neurodegenerative disorders. This review highlights the emerging roles of IRE1 and PERK in preserving mitochondrial function and their relevance to neurodegeneration. It also examines pharmacological strategies targeting these proteins, which influence both UPR signaling and ER-mitochondrial communication, offering a comprehensive perspective on their roles in health and disease.